Convergence in public expenditures across EU countries: Evidence from club convergence - Nicholas Apergis; Christina Christou; Christis Hassapis (Economics & Finance Research, 2013)
The goal of the present article is to investigate the degree of convergence in public expenditures for a panel of 17 European Union member countries spanning the period 1990 to 2012. We apply the methodology of Phillips and Sul (2007) various categories of public expenditures to assess the existence of convergence clubs. Overall, the results do not support the hypothesis that all countries converge to a single equilibrium state in various public expenditures.
Keywords: 330